A Systematic Review On Rural Parent Vaccine Hesitancy Related To The Administration Of the Human Papillomavirus Vaccine To Adolescent Children - Hewett, Sydney E (East Carolina University, 2021)
Despite evidence of the significant individual and community benefit of vaccinations, vaccine hesitancy is an ongoing obstacle for both health care providers and public health professionals. Vaccine hesitancy is often informed by religious and social ideologies, as well as debunked studies and misinformation. The impact of these ideologies is particularly true in the case of Human Papillomavirus (HPV). As a sexually transmitted infection, this hesitancy is tightly bound to socially constructed ideas of sexuality and gender. This is particularly true in the case of parental hesitancy for adolescent patients. In order to promote vaccination in this population, it is critical to understand the beliefs and ideologies informing this hesitation to vaccinate adolescents. Research has shown that reasons for parental hesitancy and refusal can vary based on demographics such as: location, religion, socio-economic status, and education-level, among others. Within this growing literature, the majority of studies have focused on urban areas with limited attention focused on rural areas. This systematic review examines parental vaccine hesitancy in rural populations considering the HPV vaccine.
Keywords: Human Papillomavirus; Vaccine Hesitancy; Rural Health